2018
DOI: 10.1002/bmc.4252
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 20(S)‐protopanaxadiol and its three metabolites in rat plasma by LC–MS/MS: application to their pharmacokinetic studies

Abstract: The aim of this study was to develop an LC-MS/MS method for simultaneous determination of 20(S) protopanaxadiol (PPD) and its three metabolites, PPD-glucuronide (M1), (20S,24S)-epoxy-dammarane-3,12,25-triol (M2) and (20S,24R)-epoxydammarane-3,12,25-triol (M3), in rat plasma. Precipitation with acetonitrile was employed for sample preparation and chromatographic separations were achieved on a C column. The sample was detected using triple quadrupole tandem mass spectrometer with selected reaction monitoring mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…PPD administration of 5 mg/kg could remarkably increase the enzyme activity of AK5. To date, an increasing number of pharmacokinetic research has reported PPD concentration in plasma (0.12–10 μg/mL) after oral administration (1–100 mg/kg) with PPD or PPD dosage forms. , In addition, rat pharmacokinetic studies have reported the plasma peak concentration (0.2 or 2.7–30 μg/mL) after intragastric (25 mg/kg) or intravenous (7.5–25 mg/kg) administration once with PPD suspension or PPD dosage forms. These results showed that the PPD concentration selected in this study could reach in vivo . However, a too high concentration of PPD in vivo may affect its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…PPD administration of 5 mg/kg could remarkably increase the enzyme activity of AK5. To date, an increasing number of pharmacokinetic research has reported PPD concentration in plasma (0.12–10 μg/mL) after oral administration (1–100 mg/kg) with PPD or PPD dosage forms. , In addition, rat pharmacokinetic studies have reported the plasma peak concentration (0.2 or 2.7–30 μg/mL) after intragastric (25 mg/kg) or intravenous (7.5–25 mg/kg) administration once with PPD suspension or PPD dosage forms. These results showed that the PPD concentration selected in this study could reach in vivo . However, a too high concentration of PPD in vivo may affect its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase was composed of aqueous solution (A) and methanol (B) and was eluted at a flow rate of 0.20 mL/min following a gradient elution procedure, as shown in Table . A Waters ACQUITY triple quadrupole (TQD) mass spectrometer (Waters Corp., Manchester, U.K.) was connected to the UPLC system via an electrospray ionization (ESI) interface, which was simultaneously operated both in positive and in negative ion mode. Quantification was performed using selective ion monitoring (SIM) of m / z [M + Na] + 483.37 for PPD and m / z [M + H] + 373.96 for finasteride. ,, …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Quantification was performed using selective ion monitoring (SIM) of m/z[M + Na] + 483.37 for PPD and m/z[M + H] + 373.96 for finasteride. 14,37,41 2.5. Tissue Distribution.…”
Section: In Vivo Pharmacokinetic Studiesmentioning
confidence: 99%
“…There are numerous reports on the utilization of the LC/MS/MS method to detect ginsenosides ( Choi et al, 2016 ; Jin et al, 2019 ; Yang et al, 2019 ), panaxadiol ( Cai et al, 2013 ), and PPD, including quantitative detection in rat plasma ( Ren et al, 2008 ; Han et al, 2010 ; Wang et al, 2012 ; Bao et al, 2013 ; Zhao et al, 2016 ; Jin-Qi et al, 2018 ) as well as in human plasma and urine ( Zhang et al, 2009 ; Choi et al, 2016 ). The above articles, which focus on establishing quantitative methods, often mention the use of narrow pharmacokinetic studies (only in plasma, not involving tissue distribution, excretion, and metabolism).…”
Section: Introductionmentioning
confidence: 99%